METHODS OF TEACHING ECONOMIC DISCIPLINES IN HIGHER EDUCATION SYSTEM (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article deals with the issues of economic education in higher educational institutions and modern requirements for teaching economic disciplines